ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT IMPLEMENTASI GREEN CONSTRUCTION PADA PROYEK BANGUNAN GEDUNG DI KOTA PALANGKA RAYA - Mayang, Mayang; Nuswantoro, Waluyo; Uda, Subrata Aditama Kittie Aidon Uda (Fakultas Teknik Universitas Palangka Raya, 2026)
The construction industry is one of the primary contributors to environmental degradation through carbon emissions, excessive energy use, and waste. In response to these challenges, green construction has emerged as a sustainable development approach that minimizes negative impacts on the environment. This study employs an explanatory quantitative research method using a questionnaire survey approach. Data analysis was conducted through “validity and reliability tests” using SPSS 25.0, descriptive analysis (mean, standard deviation, and TCR), and “Structural Equation Modeling with Partial Least Squares (SEM-PLS)” for factor analysis and to test relationships between variables. Based on the results of the PLS-SEM analysis, it was found that factor X2.2 had an outer weight of 0.804, an outer weight p-value of 0.006, and an outer loading of 0.955, while factor X1.1 had an outer weight of 0.765, an outer weight p-value of 0.029, and an outer loading of 0.925. The success rate of green construction implementation stands at 36.47%, which is low. The dominant factors influencing the implementation rate of GC in building projects in Palangka Raya are financial and management/human resources factors, followed by regulatory and government factors. “The influence of each factor is as follows: regulatory and government factors have a positive and significant influence; financial and management/human resources factors also have a positive and significant influence; while technical and technological factors have a negative and insignificant influence